2018
DOI: 10.1016/j.jval.2018.04.1311
|View full text |Cite
|
Sign up to set email alerts
|

Real World Incidence and Prevalence of Low Back Pain: A Systematic Review

Abstract: Objectives: In the current era of bundled payments, greater focus has been placed on preoperative patient optimization. This study examined the prevalence of preoperative anemia from 2007-2017 among patients undergoing elective total joint arthroplasty (TJA) and its association with transfusion. MethOds: This retrospective analysis used healthcare claims data from the Optum ClinformaticsTM Data Mart database (2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017). Patient selection criteria included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Low back pain (LBP) is a worldwide problem [1,2], affecting athletes in a wide range of sports [2 -4]. Recent studies have shown that the prevalence of LBP in athletes varies by sport [4].…”
Section: Introductionmentioning
confidence: 99%
“…Low back pain (LBP) is a worldwide problem [1,2], affecting athletes in a wide range of sports [2 -4]. Recent studies have shown that the prevalence of LBP in athletes varies by sport [4].…”
Section: Introductionmentioning
confidence: 99%